Academic boredom among students in higher education: A mixed-methods exploration of characteristics, contributors and consequences. Issue 5 (3rd September 2017) - Sharp, John G.; Hemmings, Brian; Kay, Russell; Murphy, Barbara; Elliott, Sam
ABSTRACT: Academic boredom usually contributes adversely towards student engagement and performance across a diverse range of settings including universities. The formal study of academic boredom in higher education remains, however, a relatively underdeveloped field and one surprisingly neglected in the UK. Rooted in Control-Value Theory, details of a mixed-methods exploration of academic boredom among 235 final year undergraduates attending a single university in England are presented. Quantitative data included measurement using the BPS-UKHE, a revised boredom proneness scale developed for use across the sector. Qualitative data arose primarily from 10 research interviews. Findings indicate that about half of all respondents experienced the most common precursors of academic boredom at least occasionally; traditional lectures with a perceived excess and inappropriate use of PowerPoint stimulating the actual onset of boredom more than other interactive forms of delivery. Coping strategies included daydreaming, texting and turning to social media. Academic boredom also occurred during the completion of assignments used to assess modules. Differences between those more prone to academic boredom than others extended to self-study (fewer hours), attendance (good rather than excellent) and degree outcome (lower marks). Findings are considered valuable empirically and theoretically, leading to recommendations surrounding boredom mitigation which challenge cultural traditions and pedagogical norms.